Media Campaign Strategies, Awareness of Breast Cancer and the Practice of Breast Self-Examination among Rural Women in Adamawa State, Nigeria - Jegede, Omolayo Olusola; Ekeh, Charles Maduabuchi; Elon, Elina (NIU Journal of Social Sciences; Vol 7 No 1 (2021): KIU Journal of Social Sciences, Vol. 7 No. 1, March 2021, 2021)
Breast Cancer has emerged as one of the major issues of public health all over the world. It has been identified as one of the most common cancers and a leading cause of deaths among thousands of women worldwide. The media is also assumed to be at the fore front in providing behavior change information. These, motivated this quantitative study, using descriptive survey research design.  Anchored on Health Belief Model and Attitude Change theory, the study found  that awareness about breast cancer and breast self-examination is high (95.7%) among rural women in Adamawa State, however, only 19.7% of the respondents indicated that they carry out breast self-examination regularly, whereas 50.5% said they do not carry out BSE regularly. This finding calls for concern as it defeats the main aim for which the media campaigns were launched in the first instance, which is to enhance the knowledge of rural women about breast cancer and breast self-examination as well as encourage them to practice breast self-examination as a cost effective and reliable method of early detection of breast cancer.